Evaluation of Frequency, Clinical Correlation, and Antibodies Confirmation Profile in Patients with Suspected Antiphospholipid Syndrome - Martins, Filipe F.; Campos, Teresa M. L. (TH Open, 2021)
Antiphospholipid syndrome (APS) is a systemic autoimmune disease characterized by arterial and venous thrombotic manifestations and/or pregnancy-related complications in patients with persistent antiphospholipid (aPL) antibodies. The introduction of Sapporo's classification criteria allowed uniformity in the classification of this pathology, representing a considerable advance in its diagnosis. However, currently some doubts about the application of these criteria still persist. The aim of this study was to contribute to the better understanding of APS by the assessment of aPL prevalence, the association between clinical and laboratory tests, and evaluation of the aPL confirmatory profile.In this study, 1,179 samples from patients with suspected APS of both genders, without age restrictions, who were advised to test for complete aPL's profile were analyzed. The samples were tested for lupus anticoagulant (LAC), anticardiolipin immunoglobulin (Ig) G/IgM and anti-β-2-glycoprotein I IgG/IgM antibodies. Patient samples with isolated test requests for analysis and samples from patients under the influence of anticoagulants or in an infectious process were excluded.The overall positivity found was 17.9% and the most frequent aPL was LAC. The antibodies were determined in isolation and in association. The prevalence of triple positivity was 0.8% and double positivity was 1.8%. Positivity was higher in inpatient/emergency services compared with outpatient services. There was a higher positivity in individuals over 41 years, males, patients with systemic lupus erythematosus, kidney complications, and deep vein thrombosis/thrombophlebitis. The positivity confirmation with second sample was 39.5% and the confirmation profile shows that 50.6% of samples confirmed with same positivity profile; 17.3% with a different profile and regarding to these, 2.5% of the samples confirmed positivity with a different antibody from the previously detected.This study suggests that the aPL's positivity tends to increase with age, showing that the aPL's testing should be avoided during an acute event and reinforces the need for complete aPL laboratory profile in the second sample and subsequent determinations.
Keywords: antiphospholipid syndrome; antiphospholipid antibodies; anticardiolipin; anti-β2-glycoprotein I; lupus anticoagulant; thrombosis